Varstvo pred ponaredki - Grlić, Andrejka (Pravni letopis, 2015)
"Promoting compliance and enforcing rules should be left to market forces, private sector and civil society actions wherever possible. Inspections and enforcement cannot be everywhere and address everything, and there are many other ways to achieve regulations objectives." I agree and support the recommendation of the OECD even when we talk about IPR.1
Keywords: blagovne znamke; industrijska lastnina; nelojalna konkurenca; ponaredki